Coping Strategies and Psychological Outcomes: The Moderating Effects of Personal Resiliency. Issue 3 (2nd April 2016) - Smith, Martin M.; Saklofske, Donald H.; Keefer, Kateryna V.; Tremblay, Paul F.
ABSTRACT: Certain coping strategies alleviate stress and promote positive psychological outcomes, whereas others exacerbate stress and promote negative psychological outcomes. However, the efficacy of any given coping strategy may also depend on personal resiliency. This study examined whether personal resiliency moderated the effects of task-oriented, avoidance-oriented, and emotion-oriented coping strategies on measures of depression, anxiety, stress, positive affect, negative affect, and satisfaction with life. Results ( N = 424 undergraduates) showed higher personal resiliency was associated with greater use of task-oriented coping strategies, which were in turn associated with more adaptive outcomes, and less reliance on nonconstructive emotion-oriented strategies, which in turn were associated with poorer psychological outcomes. In addition, individual differences in personal resiliency moderated the effects of task-oriented coping on negative affect and of emotion-oriented coping on negative affect and depression. Specifically, proactive task-oriented coping was associated with greater negative affect for people lower in personal resiliency. Moreover, high personal resiliency attenuated the negative effects of emotion-oriented coping on depression and negative affect. The effects of avoidance-oriented coping were mixed and were not associated with or dependent on levels of personal resiliency.